Dietary supplementation with n-3-fatty acids in patients with pancreatic cancer and cachexia: marine phospholipids versus fish oil - a randomized controlled double-blind trial - Kristin Werner (Lipids in Health and Disease, 2017)
Abstract Background Like many other cancer patients, most pancreatic carcinoma patients suffer from severe weight loss. As shown in numerous studies with fish oil (FO) supplementation, a minimum daily intake of 1.5 g n-3-fatty acids (n-3-FA) contributes to weight stabilization and improvement of quality of life (QoL) of cancer patients. Given n-3-FA not as triglycerides (FO), but mainly bound to marine phospholipids (MPL), weight stabilization and improvement of QoL has already been seen at much lower doses of n-3-FA (0,3 g), and MPL were much better tolerated. The objective of this double-blind randomized controlled trial was to compare low dose MPL and FO formulations, which had the same n-3-FA amount and composition, on weight and appetite stabilization, global health enhancement (QoL), and plasma FA-profiles in patients suffering from pancreatic cancer. Methods Sixty pancreatic cancer patients were included into the study and randomized to take either FO- or MPL supplementation. Patients were treated with 0.3 g of n-3-fatty acids per day over six weeks. Since the n-3-FA content of FO is usually higher than that of MPL, FO was diluted with 40% of medium chain triglycerides (MCT) to achieve the same capsule size in both intervention groups and therefore assure blinding. Routine blood parameters, lipid profiles, body weight, and appetite were measured before and after intervention. Patient compliance was assessed through a patient diary. Quality of life and nutritional habits were assessed with validated questionnaires (EORTC-QLQ-C30, PAN26). Thirty one patients finalized the study protocol and were analyzed (per-protocol-analysis). Results Intervention with low dose n-3-FAs, either as FO or MPL supplementation, resulted in similar and promising weight and appetite stabilization in pancreatic cancer patients. MPL capsules were slightly better tolerated and showed fewer side effects, when compared to FO supplementation. Conclusion The similar effects between both interventions were unexpected but reliable, since the MPL and FO formulations caused identical increases of n-3-FAs in plasma lipids of included patients after supplementation. The effects of FO with very low n-3-FA content might be explained by the addition of MCT. The results of this study suggest the need for further investigations of marine phospholipids for the improvement of QoL of cancer patients, optionally in combination with MCT.